Charm and beauty isolation from heavy flavor decay electrons in Au+Au collisions at sNN = 200 GeV at RHIC - Fan Si; Xiao-Long Chen; Long Zhou; Yi-Fei Zhang; Sheng-Hui Zhang; Xin-Yue Ju; Xiu-Jun Li; Xin Dong; Nu Xu (Physics Letters B, 2020)
We present a study of charm and beauty isolation based on a data-driven method with recent measurements on heavy flavor hadrons and their decay electrons in Au+Au collisions at sNN = 200 GeV at RHIC. The individual electron pT spectra, RAA and v2 distributions from charmed and beauty hadron decays are obtained. We find that the electron RAA from beauty hadron decays (RAAb→e) is suppressed in minimum bias Au+Au collisions but less suppressed compared with that from charmed hadron decays at pT > 3.5 GeV/c, which indicates that beauty quark interacts with the hot-dense medium with depositing its energy and is consistent with the mass-dependent energy loss scenario. For the first time, the non-zero electron v2 from beauty hadron decays (v2b→e) at pT > 3.0 GeV/c is observed and shows smaller elliptic flow compared with that from charmed hadron decays at pT < 4.0 GeV/c. At 2.5 GeV/c < pT < 4.5 GeV/c, v2b→e is smaller than a number-of-constituent-quark (NCQ) scaling hypothesis. This suggests that beauty quark is unlikely thermalized and too heavy to be moved in a partonic collectivity in heavy-ion collisions at the RHIC energy.